Nudging healthcare workers: assessing the impact of pre-booked appointments on influenza vaccination uptake - Daicampi, Chiara; Cesaro, Elisabetta; Kolmykova, Taisiia; Degan, Mario; Baldo, Vincenzo (Frontiers in Public Health, 2025)
BackgroundInfluenza vaccination coverage among healthcare workers in Italy remains low compared with international benchmarks. Evidence on effective and scalable interventions in hospital settings is limited.MethodsWe conducted a clustered quasi-experimental study in a large Italian university hospital, comparing the 2024/25 campaign to 2023/24. Hospital cost centers (n = 277) were non-randomly allocated to intervention (personalized letter with a pre-scheduled on-site appointment; 130 centers, 2,967 healthcare workers) or control (standard information; 147 centers, 1,577 healthcare workers). Administrative records provided uptake. We estimated Difference-in-Differences models at the cost-center level, weighting by center size and clustering standard errors at cost-center level, with subgroup analyzes by profession, gender, and age.ResultsOverall coverage increased from 16.0% in 2023/24 to 25.2% in 2024/25. The DiD analysis indicated a significant effect of invitation letters (+4.0 percentage points). Stratification showed heterogeneous responses: the intervention was particularly effective among nurses, female workers, and mid-aged staff, while no effect was observed among physicians, the youngest, and the oldest age groups.ConclusionPersonalized invitation letters with pre-scheduled appointments represent a simple, scalable, and resource-efficient strategy to increase influenza vaccination uptake among HCWs. However, the effect was not homogeneous across subgroups, highlighting the importance of tailoring communication strategies to different professional and demographic profiles.